2019
DOI: 10.3892/etm.2019.7720
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA H19 knockdown inhibits the cell viability and promotes apoptosis of thyroid cancer cells through regulating the PI3K/AKT pathway

Abstract: Certain long non-coding (lnc)RNAs have been reported to serve important roles in the genesis and progression of thyroid cancer (TC). Recent studies have demonstrated that the expression of lncRNA H19 is upregulated in TC tissues; however, knowledge of the associated molecular mechanisms is limited. Therefore, the present study aimed to clarify the roles of H19 in TC. The mRNA expression of lncRNA H19 in TC tissues was determined using reverse transcription-quantitative polymerase chain reaction analysis, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…Accumulating evidence has revealed that H19, as a cancer-related lncRNA, served an important role in physiological activities and pathological mechanisms ( 16 , 28 , 29 ). For example, H19 was reported to act as an oncogene in bladder, gastric, breast and thyroid cancer, in addition to glioma ( 15 , 30 33 ). In colorectal cancer, H19 promoted the cell proliferation, migration and invasion of cancer cells through sponging miR-138 and subsequently upregulating the expression levels of HMGA1 ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence has revealed that H19, as a cancer-related lncRNA, served an important role in physiological activities and pathological mechanisms ( 16 , 28 , 29 ). For example, H19 was reported to act as an oncogene in bladder, gastric, breast and thyroid cancer, in addition to glioma ( 15 , 30 33 ). In colorectal cancer, H19 promoted the cell proliferation, migration and invasion of cancer cells through sponging miR-138 and subsequently upregulating the expression levels of HMGA1 ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…H19, located on chromosome 11p15.5, is a long non-coding RNA (lncRNA) which was initially termed as an oncofetal transcript ( 12 ). The aberrant expression of H19 was revealed to participate in the pathogenesis of several types of human cancer, including bladder, breast, thyroid and hepatocellular carcinoma ( 13 15 ). In addition, a previous study suggested that H19 may be regarded as a biomarker for numerous types of cancer and a potential therapeutic target ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, KEGG terms such as transcriptional misregulation in cancer, Rap1 signaling pathway and PI3K-Akt signaling pathway were obtianed. PI3K-Akt signaling pathway had been reported to play an important role in the development of thyroid cancer [46,47], breast cancer [48], colorectal cancer [49], non-small cell lung cancer [50] and gastric cancer [51] etc.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] As one of the earliest lncRNAs found, H19 (also an oncogene) is located on chromosome 11 and highly expressed in various tumors. 8,9 In our study, we explored the role and mechanism of action of H19 in GC. H19 rose in tissues, serum and cells of GC patients, and this increased RNA was related to a tumor size ≥5 cm, high stages (III+IV), lymph node metastasis and a poor survival rate.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 7 Having found to be highly expressed in various tumors, lncRNA H19 ( H19 ) is a member of lncRNAs and is considered as a tumor promoter. For instance, it plays a carcinogenic role in thyroid cancer through PI3K/AKT pathway, 8 and promotes lung cancer cells to proliferate and invade by regulating markers for epithelial-mesenchymal transition. 9 Additionally, it upregulates in GC and predicts the poor prognosis of patients, so downregulating its expression can inhibit gastric cancer cells (GCCs) to invade and migrate.…”
Section: Introductionmentioning
confidence: 99%